KONSEP DALAM MERUMUSKAN VISI, MISI, TUJUAN DAN PROGRAM LEMBAGA PENDIDIKAN ISLAM - Fikri, Moch Sulton Al; Nabila, Sayyid Qutub; Arianto, Aji; Yuliastutik, Yuliastutik (SKILLS : Jurnal Riset dan Studi Manajemen Pendidikan Islam, 2024)
The era of Society 5.0 and Industrial Revolution 4.0 brought fundamental changes to the educational landscape, requiring Islamic educational institutions to adapt without losing their identity. This article examines the concept of formulating the vision, mission, goals and programs of Islamic educational institutions in the context of the digital era. This research uses a library research method with a descriptive-analytical approach. Data was obtained from primary sources in the form of the Al-Qur'an, Hadith, and the latest publications from reputable Islamic education journals, as well as relevant secondary sources. Data analysis was carried out through the stages of categorization, contextual interpretation and conceptual synthesis. The research results show that these four elements must be formulated based on the integration of modern management and Islamic values ​​interpreted contextually. The main finding is the concept of "technological ijtihad", namely an effort to reinterpret classical Islamic concepts to make them relevant to the digital era. The vision must respond to global issues, the mission includes Islamic "digital citizenship", the goals are formulated using SMART and VUCA Prime principles, while the program integrates Islamic boarding school values ​​with technology. This approach resulted in a creative synthesis between tradition and modernity, which gave birth to a "techno-spiritual" generation. This article contributes to providing a conceptual framework for Islamic educational institutions to formulate strategic directions that are in line with Islamic identity and the demands of the times, so that they can produce graduates who are superior intellectually, technologically and spiritually.